Top Management Team Diversity and the moderating effect of Discretionary Accounting Choices on Financial Reporting Quality among Commercial State Corporations in Kenya - Omoro, Nixon Oluoch (Journal of Accounting, Business and Finance Research, 2020)
The study aims to examine the moderating effect of discretionary accounting choices on the relationship between top management demographic diversity and financial reporting quality among state commercial firms in Kenya based on 248 firm-year observations for 2004 -2015. The study used correlational research design to achieve the sought objectives. It lays a broad foundation for the future research work into the theory and practice of financial reporting quality in commercial state corporations. The findings clearly reveal that, there exist both positive and negative relationship between discretionary accounting choices and financial reporting quality. However, the relationship varies with each financial reporting quality proxy measures. The demographic variables that were statistically significant in explaining FRQ were; age, education, tenure, gender and functional background diversity. Hence, managerial characteristics matter in explaining discretionary accounting choices and financial reporting quality in the companies. Despite the findings showed minimal significant effects on earnings quality and timeliness. Discretionary accounting choices should not be used by the management opportunistically but should be used to enhance quality reporting. The study recommends that stakeholders in commercial state corporations should ensure that discretionary accounting choices is improved to decrease manipulations of accounting information in order to increase the quality of reporting.